A Pilot Scale Study of Cenosphere Recovery and Concentration using the Inverted Reflux Classifier. (August 2015) - Kiani, A.; Zhou, J.; Galvin, K.P.
Highlights: The Inverted Reflux Classifier was scaled up, separating cenospheres from fly ash. The benefit of combined inclined settling and streaming phenomenon was confirmed. A clear basis for industrial operation was established. Abstract: Cenospheres are hollow spherical particles formed as part of the fly ash waste of coal-fired power stations. In a previous paper Kiani et al. (2015) investigated the recovery and the concentration of these particles using an Inverted Reflux Classifier (IRC) at a laboratory scale, of cross-section 0.100 m × 0.086 m, achieving a throughput advantage over a conventional fluidized bed by a factor of 54. The present paper investigated the potential to achieve scale-up, utilizing a pilot scale device with cross-section 0.3 m × 0.3 m. The product grade and recovery were examined as a function of the solids yield by varying the product volumetric rate relative to the feed volumetric rate. The performance data were compared directly with those obtained at the smaller laboratory scale. Agreement was excellent. The performance was also examined as a function of the feed slurry flux, with good agreement again evident at the laboratory and pilot scales. Overall, the separation performance was excellent, with a cenosphere recovery of about 80% achievable at a high upgrade of 19 while a recovery of 75% was achieved at an upgrade of 38. Here the feed solids flux was 4.2 t/(m 2 h). It is noted that much higher upgrade was achieved at a recovery of about 80% in the former study by operating at a lower solids feed flux. This paper provides the necessary basis for proceeding with a full scale implementation of this technology.